Prevalence and risk factors of upper gastrointestinal symptoms in community pharmacies in Spain: a cross-sectional study - Puig-Moltó, María; Lumbreras, Blanca; López-Pintor, Elsa (Frontiers in Pharmacology, 2023)
Background: Frequently, the community pharmacies are the only points of consultation for upper-gastrointestinal symptomology. However, the heterogeneity of symptoms often limits the correct management of the patient. The study aim is to describe the epidemiological characteristics of patients with upper-gastrointestinal symptoms who ask for advice in community pharmacies. Methods: A cross-sectional study was performed in 134 Spanish pharmacies (June-October 2022) and we included 1,360 patients. We collected sociodemographic, clinical variables and current medication data. The pharmacist evaluated the gastrointestinal symptoms through the application of the GERD Impact Scale (GIS questionnaire). Patients were classified into three groups according to their symptoms: epigastric, retrosternal and overlapping symptoms. Results: Median age was 49 years (interquartile range 36-62 years) and 59.3% were women. Most patients reported overlapping symptoms (738, 54.3%), 433 (31.8%) retrosternal and 189 (13.9%) epigastric symptoms. Patients with overlapping symptoms were more likely to associated consumption of foods and/or drinks and symptoms and showed lower scores on the GIS scale (median 26, IQR 20-30) than those with epigastric (median 32, IQR 29-33) and retrosternal (median 32, IQR 28-34) symptoms (p<0.001). Patients in treatment with a combination of alginates and antiacids were more likely to think that it better alleviated their symptoms in all the patients included (p=0.012). Conclusions: More than half of the patients showed overlapping symptoms, and were more likely to associate their symptoms with dietary habits and having poorer scores in the GIS scale. Clinical awareness of such overlapping condition would help optimize the management of patients with upper gastrointestinal symptoms in practice.